Summability, Some Sequence, Some Sequence Spaces and Their Matrix Transformations - Ray, Suresh; Shrestha, Shailendra Kumar (Journal of Advanced Academic Research, 2015)
The most general linear operator to transform from new sequence space into another sequence space is actually given by an infinite matrix. In the present paper we represent some sequence spaces and their matrix transformations and summability. Journal of Advanced Academic Research Vol.1(1) 2014: 29-35